Pseudo-Cerebrospinal Fluid Leaks of the Anterior Skull Base: Algorithm for Diagnosis and Management - Constanzo, Felipe; Pinto, Jaime; Sedaghat, Sahba; Schmidt, Thomas (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Pseudo-cerebrospinal fluid (CSF) leaks are a rare cause of unilateral, watery rhinorrhea. We proposed a step-wise approach to evaluate these cases.Design It involves a single-center retrospective cohort study.Setting The setting is that of a tertiary academic medical center.Participants Ten patients with diagnosis of pseudo-CSF leak over a 21-year period were evaluated using our proposed algorithm that includes computed tomography, magnetic resonance imaging, nasal endoscopy, β-2 transferrin, intrathecal fluorescein, and surgical exploration of the anterior cranial base.Main Outcome Measures The occurrence of intracranial infection and resolution of the symptoms were evaluated at a mean follow-up of 94.4 months.Results Eight patients had history of skull base fracture or surgery. In all patients computed tomography, magnetic resonance imaging, and nasal endoscopy did not show signs of CSF leak. Beta-2 transferrin testing was performed in five patients, being negative in all of them. Intrathecal fluorescein was performed in seven patients, being negative in five and inconclusive in two. Surgical exploration was performed in five patients, definitively ruling out CSF leak. Six patients were treated with intranasal ipratropium, resolving the symptoms in all cases.Conclusion The presented algorithm provides a step-wise approach for patients with unilateral watery rhinorrhea, allowing to safely ruling out CSF leak.
Keywords: Pseudo-CSF leaks; CSF leaks; skull base surgery; meningitis